2021
DOI: 10.1002/anie.202111385
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Dissociation of a Dialumene**

Abstract: Dialumenes are neutral Al I compounds with Al = Al multiple bonds.Wereport the isolation of an amidophosphinesupported dialumene.O ur X-ray crystallographic,s pectroscopic,a nd computational DFT analyses reveal al ong and extreme trans-bent Al=Al bond with alow dissociation energy and bond order.Insolution, the dialumene can dissociate into monomeric Al I species.Reactivity studies reveal two modes of reaction:asdialumene or as aluminyl monomers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
1
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 44 publications
5
61
1
11
Order By: Relevance
“…[30] Eine C4-B2-Bindungswechselwirkung in 8' ' wird auch durch Berechnungen der Mayerschen Bindungsordnung (MBO), des WBI und der Fuzzy-Bindungsordnung (FBO) unterstützt, wobei C4-B2-Bindungsordnungen von 0.47, 0. Angesichts der etablierten Dissoziation gewisser Alkene, [31] Alkenanaloga von Al [32] sowie anderen Elementen der Gruppe 14 (Si, Ge,S n, Pb), [33] wodurch die entsprechenden Carbene und Carbenanaloga gebildet werden, und der Tatsache,d ass CAACsi nd er Lage sind, zweifach koordinierte Borylene zu stabilisieren, [4] 9) und 1.633( 7) ), fällt aber in den Bereich beschriebener B=C-Doppelbindungen in Basen-stabilisierten Boraalkenen (1.43-1.50 ) [2b, 3b,34] und ist…”
Section: Ergebnisse Und Diskussionunclassified
“…[30] Eine C4-B2-Bindungswechselwirkung in 8' ' wird auch durch Berechnungen der Mayerschen Bindungsordnung (MBO), des WBI und der Fuzzy-Bindungsordnung (FBO) unterstützt, wobei C4-B2-Bindungsordnungen von 0.47, 0. Angesichts der etablierten Dissoziation gewisser Alkene, [31] Alkenanaloga von Al [32] sowie anderen Elementen der Gruppe 14 (Si, Ge,S n, Pb), [33] wodurch die entsprechenden Carbene und Carbenanaloga gebildet werden, und der Tatsache,d ass CAACsi nd er Lage sind, zweifach koordinierte Borylene zu stabilisieren, [4] 9) und 1.633( 7) ), fällt aber in den Bereich beschriebener B=C-Doppelbindungen in Basen-stabilisierten Boraalkenen (1.43-1.50 ) [2b, 3b,34] und ist…”
Section: Ergebnisse Und Diskussionunclassified
“…CAA-CAlCl 3 , CAAC = 1-(2,6-diisopropylphenyl)-3,3,5,5tetramethyl-pyrrolidin-2-ylidene) has been shown to produce either Me 2 IPr-dialumene adducts by Inoue [24] or a bis-CAAC-stabilized aluminium radical by Roesky, Frenking et al [25] Based on chemical trapping experiments, Cowley and Krämer indicated the transient existence of an amidophosphine-supported aluminylene E that is in equilibrium with its dimeric dialumene in solutions. [26] E has been described as a highly fleeting species, defying direct observation. [26,27] In the present work, we propose a general concept for boosting the redox activity of aluminylenes by simple addition of a Lewis basic NHC, leading to an isolable acyclic NHC-stabilized aluminylene 2 (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…The first is a silyl-substituted dialumene by Inoue et al 14 followed by an aryl analogue 15 and an amidophosphinestabilized AlvAl double bond. 16 In spite of the several reports of compounds with Al-Al and Ga-Ga bonds, PhC(N t Bu) 2 (amidinate) stabilized double bonds are not known in the literature, although amidinates are widely used to stabilize compounds of low valent elements. It has been reported that an amidinate ligand stabilized the Si(I)-Si(I) bond.…”
Section: Introductionmentioning
confidence: 99%